Kecerdasan Emosi pada Siswa yang Orang tuanya Bercerai dan Tidak Bercerai (Utuh) - Nolasari, Tiwi; Ervina, Iin; Istiqomah (Indonesian Journal Publisher, 2024)
The emergence of deviant behavior among teenagers is caused by the inability of teenagers to control their emotions. Adolescents' tendencies to behave deviantly can be controlled if adolescents have well-developed emotional intelligence. Good emotional intelligence can help teenagers manage their emotions appropriately so they can adapt to their environment. Family is one of the factors that influences emotional intelligence, because the relationship between parents and teenagers will have an impact on teenagers' emotional intelligence. The aim of this research is to determine the differences in emotional intelligence of students whose parents are divorced and who are not divorced (intact) at SMA PGRI Purwoharjo. This research is acomparative quantitative research on 38 students whose parents were divorced and 38 students whose parents were not divorced (intact) at SMA PGRI Purwoharjo, which was obtained using quota sampling techniques. This research uses an emotional intelligence scale (30 items, α = 0.866) adapted from research by Wardani (2019). The results of this study show that there is no difference in emotional intelligence between students whose parents are divorced and not divorced (intact) at SMA PGRI Purwoharjo (r = 0.759, p > 0.05).